RELATIVE EFFICACY OF AM FUNGI ON GUIZOTIA ABYSSINICA (L.F) CASS., (NIGER) - H.C.LAKSHMAN (International Journal of Pharma and Bio Sciences, 2014)
Experiments were conducted to understand the relative efficacy of AM fungi on Niger under experimental conditions. Plants were inoculated with three AM fungi in different factorial combinations. The plants inoculated with three AM fungi as triple inocula (Glomus macrocarpum, Gigaspora margarita and Sclerocystis clavispora) brought significantly increase in plant growth growth parameters and biomass yield. Hence inoculation with Glomus macrocarpum+Gigaspora margarita + Sclerocystis clavispora was found to be better than the single or dual inoculated AM fungi and also over the non-inoculated plants.